Biodiesel production by direct esterification of fatty acids with propyl and butyl alcohols - Ferial A. Zaher; Hanaa M. Soliman (Egyptian Journal of Petroleum)
The expected depletion of natural petroleum resources in the near future and pollution of the environment due to excessive carbon dioxide emissions by fossil fuel and its adverse effect on global warming constitute two major problems facing the whole world. In view of these problems, much research work is now directed worldwide to find fuels alternative to those derived from petroleum which should be renewable and more environmentally friendly fuels. Biodiesel fuel which is a blend of fatty acid esters with alcohols is considered the most suitable alternative fuel for diesel engines. In this scope of research work, a previous study (Soliman et al., 2013) has been made to explore the opportunity of utilizing the fatty acids that can be obtained from the waste of edible oil industry in Egypt to produce biodiesel fuel by direct esterification with methanol as well as ethanol in the presence of sulfuric acid as a catalyst. This paper is a continuation of that work where two other alcohols of a chain length longer than ethanol have been used being propanol and butanol. The performance of a diesel engine running using a 50% blend of regular diesel fuel and each of the two biodiesels prepared was compared to that using regular diesel fuel. The results have shown that the brake specific fuel consumption (BSFC) and the brake thermal efficiency at full engine loading were almost the same in all cases. This indicates that the produced fuel could be used as an efficient fuel substitute for diesel engines. By comparing the results of the present work to those reported in our previous work, it appeared that methanol which has the shortest carbon chain length is the most recommended in view of the brake thermal efficiency of a diesel engine at full loading.